Leishmania infantum recombinant kinesin degenerated derived repeat (rKDDR): A novel potential antigen for serodiagnosis of visceral leishmaniasis. - Lucas Dhom-Lemos; Agostinho Gonçalves Viana; João Luis Reis Cunha; Mariana Santos Cardoso; Tiago Antônio Oliveira Mendes; Guilherme Rafael Gomide Pinheiro; Williane Fernanda Siqueira; Francisco Pereira Lobo; Leandro Freitas Teles; Lilian Lacerda Bueno; Silvio Fernando Guimarães-Carvalho; Daniella Castanheira Bartholomeu; et al. (PLoS ONE, 2019)
Visceral leishmaniasis (VL) or kala-azar, the most severe form of leishmaniasis, can lead to death if not properly diagnosed and treated. Correct identification of infected patients and reservoirs is vital for controlling the spread of leishmaniasis. Current diagnostic kits for leishmaniasis show high sensitivity and specificity, but can also result in false negatives and cross reactions with related parasitic infections. New diagnostic methods with greater accuracy are urgently needed for diagnosis of leishmaniasis. In this study, we aimed to uncover a new highly effective antigen for the diagnosis of visceral leishmaniasis in dogs and humans, aiming to improve the accuracy compared with those of current methods of diagnosis. Initially, in-silico epitope prediction analyses identified several potential B-cell epitopes in the repetitive region of Leishmania infantum kinesin, which co-localized with predicted structural disordered regions, suggesting high potential for antigenicity. Based on this analysis, 8.5 genomic motifs, which encode the repetitive sequence of 39 degenerate amino acids, were selected for recombinant expression. BLASTn analysis of this repetitive region indicated that it is absent in the T. cruzi parasite, which is closely related to Leishmania, indicating the specificity of this region. This potentially antigenic protein, named recombinant kinesin degenerated derived repeat (rKDDR), was recombinantly expressed in Escherichia coli BL21-Star using the pET28a-TEV expression vector. We then evaluated the performance of rKDDR in correctly diagnosing Leishmania infection and compared this new assay with currently used diagnostic tests for leishmaniasis. rKDDR showed greater sensitivity and specificity in correctly diagnosing leishmaniasis both in human (sensitivity 92.86% and specificity 100%) and canine (sensitivity 88.54% and specificity 97.30%) sera compared with those of rK39 (human: sensitivity 90.48% and specificity 97.92%; canine: sensitivity 78.13% and specificity 90.09%). In addition, the rKDDR-ELISA outperformed the EIE-LVC kit, which is the serologic kit recommended by the Brazilian Ministry of Health for the diagnosis of canine visceral leishmaniasis. These results indicate that rKDDR is a highly promising candidate for diagnosis of visceral leishmaniasis, and is more accurate than the currently used gold-standard antigens.